Assistência Técnica no Desenvolvimento do Curso Literacia Digital - MAURÍCIO JORNADA BASTOS (2025)
This work, developed within the scope of a Supervised Teaching Project, details the provision of technical assistance to enhance the "Digital Literacy" extension course. The main objective was to convert the educational material, originally available in a repository with Jupyter notebooks and Markdown files, into an accessible and structured website. The implementation was carried out manually, using the university's WordPress platform to create a post hierarchy that mirrors the structure of the course chapters. As a result, the website was successfully deployed, organizing all content into an easy-to-navigate platform and significantly improving the learning experience and student access to the material.